Pengaruh Corporate Social Responsibility Disclosure, Kepemilikan Institusional, Leverage, Dan Pertumbuhan Aset Terhadap Nilai Perusahaan - Yeni Alfiana; Aries Veronica; Dwi Yanti; Wiwin Winarsih; Putri Putri (UNIVED Press, 2023)
The aims of this study are: To find out how the influence of CSRD, institutional ownership, leverage and asset growth on firm value in construction, property and real estate companies listed on the Indonesian stock exchange. This research design includes the type of associative research, namely research that seeks the influence or relationship of two or more variables. Based on the type of data, this research is classified as quantitative research, namely research that uses numbers. Simultaneously or simultaneously (the results of statistical F test) show that there is no influence between CSRD, Institutional Ownership, Leverage, and Asset Growth on Firm Value in Construction, Property and Real Estate companies listed on the Indonesian stock exchange. Partially (t-test results) show that CSRD (X1) has no effect on Firm Value (Y), Institutional Ownership (X2) has no effect on Firm Value (Y), Leverage (X3) has no effect on Firm Value (Y), and Asset Growth (X4) has no effect on Firm Value in Construction, Property and Real Estate companies listed on the Indonesian stock exchange